Complement Inhibition Alleviates Cholestatic Liver Injury Through Mediating Macrophage Infiltration and Function in Mice - Guo, Zhenya; Chen, Junze; Zeng, Yonglian; Wang, Zefeng; Yao, Mei; Tomlinson, Stephen; Chen, Bin; Yuan, Guandou; He, Songqing (Frontiers in Immunology, 2022)
Background and Aims Cholestatic liver injury (CLI), which is associated with inflammatory reactions and oxidative stress, is a serious risk factor for postoperative complications. Complement system is involved in a wide range of liver disorders, including cholestasis. The present study assessed the role of complement in CLI and the therapeutic effect of the site-targeted complement inhibitor CR2-Crry in CLI. Methods Wild-type and complement gene deficient mice underwent common bile duct ligation (BDL) to induce CLI or a sham operation, followed by treatment with CR2-Crry or GdCl3. The roles of complement in CLI and the potential therapeutic effects of CR2-Crry were investigated by biochemical analysis, flow cytometry, immunohistochemistry, ELISA, and quantitative RT-PCR. Results C3 deficiency and CR2-Crry significantly reduced liver injuries in mice with CLI, and also markedly decreasing the numbers of neutrophils and macrophages in the liver. C3 deficiency and CR2-Crry also significantly reduced neutrophil expression of Mac-1 and liver expression of VCAM-1. More importantly, C3 deficiency and CR2-Crry significantly inhibited M1 macrophage polarization in these mice. Intravenous injection of GdCl3 inhibited macrophage infiltration and activation in the liver. However, the liver injury increased significantly. BDL significantly increased the level of lipopolysaccharide (LPS) in portal blood, but not in peripheral blood. GdCl3 significantly increased LPS in peripheral blood, suggesting that macrophages clear portal blood LPS. Oral administration of ampicillin to in GdCl3 treated mice reduced LPS levels in portal blood and alleviated liver damage. In contrast, intraperitoneal injection LPS increased portal blood LPS and reversed the protective effect of ampicillin. Interestingly, C3 deficiency did not affect the clearance of LPS. Conclusions Complement is involved in CLI, perhaps mediating the infiltration and activation of neutrophils and macrophage M1 polarization in the liver. C3 deficiency and CR2-Crry significantly alleviated CLI. Inhibition of complement could preserve the protective function of macrophages in clearing LPS, suggesting that complement inhibition could be useful in treating CLI.